2008
DOI: 10.5194/cp-4-357-2008
|View full text |Cite
|
Sign up to set email alerts
|

Winter temperatures in the second half of the sixteenth century in the central area of the Iberian Peninsula

Abstract: Abstract. This paper studies the winter temperatures of the second part of the sixteenth century in the central area of the Iberian Peninsula. A large number of historical documents that are stored in many different Spanish archives were consulted in order to carry out this research. The data was first arranged and weighted according to the intensity and significance of the meteorological phenomena described and, subsequently, these values were assigned an ordinal index ranging from +4 to −4. The statistical t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…The hydro-meteorological events studied here coincided with cold snaps that brought abundant episodes of snow and ice (Bullón, 2008). Temperatures returned to normal during the 1590s after 30 yr of cold conditions.…”
Section: Discussionmentioning
confidence: 98%
“…The hydro-meteorological events studied here coincided with cold snaps that brought abundant episodes of snow and ice (Bullón, 2008). Temperatures returned to normal during the 1590s after 30 yr of cold conditions.…”
Section: Discussionmentioning
confidence: 98%
“…To date, there have been few attempts to reconstruct temperatures over time in the IP due to the scarcity of information, the exception being the works by Rodrigo et al (1998) and Bullón (2008) focusing on Castile, in the central area of the IP, and for brief time periods (1634-1648, and 1550-1599, respectively). Our work represents the first attempt to reconstruct temperatures in the study region.…”
Section: Discussionmentioning
confidence: 99%
“…The construction of a regional series is justified by the analysis of the spatio-temporal variability in the region. The application of empirical orthogonal function (EOF) analysis to Andalusian stations during the period 1867(Castro-Díez et al, 2007 showed that, at seasonal and annual timescales, the first leading EOF pattern (explaining more than 50 % of the variance for both, temperature and precipitation) presents high correlations with all the stations, particularly in winter (65.69 % of explained variance for precipitation, 72.56 % for temperature). Basic statistics correspond to Mediterranean climatic characteristics, with wet and mild winters, warm and dry summers, and spring and autumn as transition seasons.…”
Section: Instrumental Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies of historical climatology carried out subsequently in Spain are laying the methodological groundwork for an www.clim-past.net/8/751/2012/objective record of the historical news relating to the climate (Barriendos, 1997;Domínguez-Castro et al, 2010;Rodrigo and Barriendos, 2008). As far as Central Spain is concerned, these events are expressed in the work of Bullón (2008), and Domínguez-Castro et al (2008). Negative pointer years are much more abundant over the 17th century, particularly in its first half, which presents the highest concentration of extreme negative years for tree growth (9 yr).…”
Section: Temporal Distribution Of Pointer Years and Their Significancmentioning
confidence: 99%